Effects of Preexposure to DEET on the Downstream Blood-Feeding Behaviors of Aedes aegypti (Diptera: Culicidae) Mosquitoes. Issue 5 (10th June 2016) - Sugiharto, Victor A.; Grieco, John P.; Murphy, Jittawadee R.; Olsen, Cara H.; Colacicco-Mayhugh, Michelle G.; Stewart, V. Ann; Achee, Nicole L.; Turell, Michael J.
Abstract: Mosquito behavior is heavily influenced by the chemical molecules in the environment. This knowledge can be used to modify insect behaviors; particularly to reduce vector–host contact as a powerful method for disease prevention. N, N -Diethyl-meta-toluamide (DEET) is the most widely used insect repellent in the market and an excellent example of a chemical that has been used to modify insect behavior for disease prevention. However, genetic insensitivity and habituation in Aedes aegypti (L.) mosquitoes after preexposure to DEET have been reported. In this study, we investigated the effect of preexposure to DEET on the downstream blood-feeding behavior of Ae. aegypti mosquitoes and the duration of the effect. We exposed mosquitoes to four different DEET concentrations: 0.10, 0.12, 0.14, and 0.16% for 10 min then allowed the mosquitoes to blood-feed on an artificial blood-feeding system either immediately or after being held for 1, 3, 6, or 24 h following DEET exposure. We found that preexposing Ae. aegypti mosquitoes to 0.14 or 0.16% DEET lowered their blood engorgement level, but did not alter their landing and probing behavior when compared to the control test populations. The reduction in complete blood-feeding was observed at all time periods tested, but was only statistically significant at 3 and 6 h after the preexposure process. Because reduction in blood meal has been associated with increased refeeding, future studies analyzing the effect of this behavior using arbovirus-infected mosquitoes are needed to address the concern of potentially increased vectorial capacity.